2017
DOI: 10.9790/3008-1201015361
|View full text |Cite
|
Sign up to set email alerts
|

Poly-𝛽-hydroxybutyrate degradation by Aspergillus fumigates isolated from soil samples collected from Jeddah, Saudi arabia

Abstract: Poly-β-hydroxybutyrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, a previous study reported that A. fumigatus was able to grow actively on natural and synthetic polyester polymers [30]. Furthermore, soil isolates of A. fumigatus were able to degrade poly-β-hydroxybutyrate acid (PHB) biopolymers [31].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, a previous study reported that A. fumigatus was able to grow actively on natural and synthetic polyester polymers [30]. Furthermore, soil isolates of A. fumigatus were able to degrade poly-β-hydroxybutyrate acid (PHB) biopolymers [31].…”
Section: Discussionmentioning
confidence: 93%
“…Scherer found that 30 • C is the optimum temperature for the growth of A. fumigatus [30]. While Aly and coworkers [31] reported that the maximum PHB depolymerase production by A. fumigatus was at pH 5 and 30 • C. In addition, Jung and his colleagues showed that A. fumigatus strain 76T-3 grew better at a temperature of 40 • C [23]. While Al Hosni and coworkers found that the most suitable temperature for A. fumigatus to biodegrade polycaprolactone (PCL) is 25-37 • C [40].…”
Section: Discussionmentioning
confidence: 99%
“…For fungi, growth on agar medium is generally more comfortable than in broth medium (Aly et al, 2017). Thus, no further assessment was conducted for isolates that showed weakly activity on solid agar medium containing PHB as a carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus has been known as one of the most predominant genera of lipase-producing and PHB-degrading molds (Matavulj and Molitoris, 1992). Some studies also reported that these molds had the ability to degrade PHB (Kumaravel et al, 2010;Lodhi, et al, 2011;Merugu, 2012;Aburas, 2016;Aly et al, 2017).…”
Section: Discussionmentioning
confidence: 99%